Macroeconomics in emerging markets - Montiel, Peter J. 1951- (Cambridge Cambridge University Press, 2011)
"The macroeconomic experience of emerging and developing economies has tended to be quite different from that of industrial countries. Compared to industrial countries, emerging and developing economies have tended to be much more unstable, with more severe boom/bust cycles, episodes of high inflation, and a variety of financial crises. This textbook describes how the standard macroeconomic models that are used in industrial countries can be modified to help understand this experience, and how institutional and policy reforms in emerging and developing economies may affect their future macroeconomic performance. This second edition differs from the first in offering - extensive new material on themes such as fiscal institutions, inflation targeting, emergent market crises, and the Great Recession - numerous application boxes - end-of-chapter questions - references for each chapter - more diagrams, less taxonomy, and a more reader-friendly narrative - enhanced integration of all parts of the work"--Provided by publisher.
Machine generated contents note: Preface; Part I. The Macroeconomic Framework: 1. Introduction and overview; 2. Concepts and definitions: the macroeconomic accounts; 3. Short-run macroeconomics and long-run growth; Part II. A Benchmark Macroeconomic Model: 4. The aggregate production function, the labor market, and aggregate supply; 5. Aggregate demand and goods market equilibrium; 6. Financial markets; 7. Short-run macroeconomic equilibrium; 8. Medium-run macroeconomic equilibrium; Part III. Public finance and macroeconomic performance: 9. The intertemporal budget constraint of the public sector; 10. Sovereign risk premia; 11. Fiscal institutions; 12. Privatization; 13. High inflation and inflation stabilization; Part IV. Monetary Institutions and Monetary Policy: 14. Monetary institutions; 15. Inflation targeting; Part V. Exchange Rate Management: 16. Equilibrium real exchange rates; 17. The benchmark model with floating exchange rates; 18. Exchange rate regimes; 19. Managing an officially-determined rate; Part VI. The Financial Sector and Macroeconomic Performance: 20. Finance, welfare, and growth; 21. Financial repression; 22. Financial reform; 23. The benchmark model with banks; 24. Coping with capital inflows; Part 7. Varieties of Emerging-Market Crises; 25. Sovereign debt crises; 26. Banking crises; 27. Currency crises and crisis interactions; 28. Lessons from the emerging market crises of the nineties; 29. Lessons from the great recession.
Acquired through Health Policy Development Program (HPDP) research grant.
Keywords: Macroeconomics; Developing countries -- Economic conditions